Feminization of survival: Socioeconomic and health consequences of male absenteeism on left behind women in Nepal - Khadka, Sujata; Gajurel, Ram Prasad (Economic Review of Nepal, 2026)
Feminization of survival is not easy, particularly in a patriarchal society after connubial bereavement or male abandonment, facing several socioeconomic or health consequences. This study thus investigates the socioeconomic and health consequences of male absenteeism on the left behind women in Nepal. This study used cross-sectional data, following mixed research methods. This study employed a structured questionnaire for a purposefully selected 73 Nepali women and 3 Nepali women for in-depth face-to-face case study interviews to triangulate and complement the survey information. This study reported that most of the women were middle-aged, literate, Hindu, of rural origin, earned just an insufficient income, lacked basic needs facilities and comforts, had no land access, had a minimal chance of alternative jobs, limited community participation, and were lone survivors. The overall findings revealed that the left behind women faced several socio-economic and health consequences, including minimal family and kin support; feeling lonely and socially withdrawn; only a threshold income for basic needs but not sufficient for food, healthcare, and parenting; deprivation of comforts; loss of emotional support; and anticipation of financial privilege from in-laws and relatives. Thus, the policymakers and stakeholders should offer economic safety nets, mental health counselling services, social awareness and teachings for social stigma reduction, clear provision of property rights and obligatory cooperation of in-laws, social networking, and parenting support to minimize socioeconomic and health consequences.